Analisis Perbedaan Perhitungan Laba Kena Pajak Menurut Laporan Keuangan Komersial dan Laporan Keuangan Fiskal - Amber Lumbantoruan (Jurnal Akuntansi, 2002)
The aim of this research is knowing the amount of the differentiation between calculation net income before tax on accounting calculation and based on taxation calculation based on Taxation Bill which available. The analysis method that used is a comparation between 2 Income Statement that degree of earning after tax is being race. The statistical approachment by using T Testing Formulan that tested by 2 edge of level significant 5% and the freedom degree is n1 + n2 – 2 are the approachment that is used in measuring the amount and impact existed in the differentiation. Based on data calculation start in the year 1997 until 2000 shows that the different in earning after tax in each year in Regular Income Statement and Fiscal Income Statement. While the result of T test found that T Calculation is -1,639 and value of –t and t table are -2,447 and 2,447 so that the differentiation is in the average of earning after tax is not so affected. Bsed on the result, it may conclude that the differentiation in each year is caused by the earning depreciation method which excludes earning taxes object and cost which is not earning consume or because the permanent different and time different exist. In order to implicate it, the company may conduct the tax plan, which available to gain especially in saving outcomes and tax fiscus division must be able to supervise the Farming Tax right in order.